Methods for the solution of boundary-value problems for weakly nonlinear integro-differential equations with parameters and restrictions - Luchka, A. Y.; Nesterenko, O. B. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We establish conditions for the existence of solutions of boundary-value problems for weakly nonlinear integro-differential equations with parameters and restrictions. We also substantiate the applicability of iterative and projection-iterative methods for the solution of these problems.